1989
DOI: 10.1210/mend-3-3-509
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Insulin-Like Growth Factor I Gene Expression in Malignancy: Evidence for a Paracrine Role in Human Breast Cancer

Abstract: Insulin-like growth factor I (IGF-I) activity has been reported to be produced by several human cancers. Identification of RNAs transcribed from the IGF-I gene has been complicated by the detection of multiple hybridizing bands on Northern analysis. To determine if any of these RNAs are transcribed from the IGF-I gene, we have used a sensitive and specific ribonuclease (RNAse) protection assay for IGF-I. We have also studied the breast cancer tissue expression of IGF-I using in situ hybridization histochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
176
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(187 citation statements)
references
References 16 publications
11
176
0
Order By: Relevance
“…Similarly stromal cells secrete both autocrine and paracrine factors. Looking at human tumor desmoplasia there are a number of autocrine and paracrine loops in play, some involving growth stimulation and some involving growth inhibition (Horgan et al, 1987;Adams et al, 1988;Osborne et al, 1989;Yee et al, 1989). PDGF, however, is the only factor out of the many growth factors secreted by breast carcinoma cells to have a sole paracrine action on neighboring stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly stromal cells secrete both autocrine and paracrine factors. Looking at human tumor desmoplasia there are a number of autocrine and paracrine loops in play, some involving growth stimulation and some involving growth inhibition (Horgan et al, 1987;Adams et al, 1988;Osborne et al, 1989;Yee et al, 1989). PDGF, however, is the only factor out of the many growth factors secreted by breast carcinoma cells to have a sole paracrine action on neighboring stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…An influence of stromal fibroblasts on the growth of breast carcinoma cells has been demonstrated in vivo (Gleiber and Schiffman, 1984). It has also been proposed that insulin-like growth factors that act synergistically with E 2 on breast cells, may also be produced by stromal cells (Yee et al, 1989;van der Burg et al, 1990). Depending on its concentration, the biological redox milieu and the involvement or induction of intracellular defence mechanisms, NO can either suppress apoptosis and eventually stimulate proliferation or activate the cell death programme (Lopez-Farre et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In situ hybridizations show that IGF-1 mRNA is expressed in the stromal cells and not by normal or malignant epithelial cells 32 . Cullen et al also showed that IGF-1 mRNA was commonly expressed in fibroblasts derived from non malignant biopsy specimens 33 .…”
Section: Igf-1 and Breast Tissuementioning
confidence: 97%